The Influence Of Motivation And Work Discipline On Employee Performance At The Office Of The Regional Disaster Management Agency Of South Bengkulu District - Satrya, Ridoh Abima; Fitriano, Yun; Putra, Iswidana Utama (Jurnal Pusat Manajemen, 2024)
Humans always play an active and dominant role in every organizational activity because humans become planners, actors, and determinants of the realization of organizational goals. The purpose of this study was to determine the effect of work motivation and work discipline on employee performance at the Office of the Regional Disaster Management Agency of South Bengkulu Regency. The sample in this study were all ASN employees at the South Bengkulu Regional Disaster Management Agency, totaling 44 ASN employees. The results of the multiple linear regression analysis are Equation: Y = 0.897 + 0.215 X1 + 0.764 X2 +e, this illustrates the positive direction of regression, meaning that the motivation variable (X1) and work discipline (X2) have a positive influence on employee performance (Y) at the South Bengkulu Regency Regional Disaster Management Agency. The magnitude of the coefficient of determination using the SPSS test can be seen that the coefficient of determination of R square is 0.902. This means that the value of motivation (X1) and the value of work discipline (X2) affect employee performance (Y) by 90.2% while the remaining 9.8% is influenced by other variables not examined in the study. The results of the t test at the 0.05 significance level explain that partially motivation and work discipline have a significant influence on employee performance at the Regional Disaster Management Agency of South Bengkulu Regency. The results of the f test at the 0.05 significance level explain that motivation, and work discipline have a simultaneously significant effect on employee performance at the South Bengkulu Regency Regional Disaster Management Agency.